Welfare and Higher Education in EU Member States - Comparative Analysis - Gabriela Wronowska (Institute of Economic Research (IER), 2014)
This paper addresses issues related to higher education in selected EU Member States and its contribution to the creation of wealth. Special emphasis was placed on the shape of education policy in selected countries through an analysis of the main indicators characterizing the same. The paper raises a number of questions which are important from the point of view of social policy: these questions relate to the policy of higher education funding and attempts to isolate and identify the relationships between higher education funding and the situation of people with higher education on the labour market. In the first part of this paper, the author presents the phenomenon of welfare by taking into account its measurement, especially those measures that relate to education related elements. Then the author indicates the relationship between education, especially its availability, and the process of wealth creation in the economy. In the empirical part of the paper an analysis is carried out on the basis of available and comparable indicators for selected EU Member States and conclusions are drawn based on the indicators.
Keywords: A11; H52; I25; I32; 330; welfare; higher education; social policy